Calculation of Cathodic Limiting Current Density in Weak Acids: Part I. Aqueous CO2 Solutions. Issue 1 (1st February 2023) - Nesic, Srdjan; Madani Sani, Fazlollah
Abstract : The limiting current density for the hydrogen evolution reaction in aqueous saturated carbon dioxide solutions needed revisiting, as the basic understanding of the underlying reaction mechanism in weak acids has changed over the past few years. We now know that the direct reduction of undissociated carbonic acid on a metal surface in aqueous carbon dioxide solutions is not significant, as was thought before, and that there is only a single dominant pathway for hydrogen evolution: reduction of free hydrogen ions. The main role of weak carbonic acid is to provide additional hydrogen ions via buffering. Therefore, a new mathematical model was needed for calculation of the limiting current density for hydrogen ion reduction, that accounts for both hydrogen ion diffusion in the boundary layer and simultaneous buffering provided by dissociation of weak carbonic acid. The new model relies on analytically solving the co-diffusion of hydrogen ions and carbonic acid in the mass transfer boundary layer, with simultaneous homogenous chemical reactions. The new expression for the limiting current density takes the form: i l i m, H + b u f f, CO 2 = F D H + e f f, CO 2 k f, CO 2 c b, CO 2 e q c b, H + e q c o t h δ m, H + δ r, H + CO 2 The performance of the new model was successfully validated by comparing it with experimental data over a broad range of conditions.